The infinite library books 1-50 - Dillon, Brian 1969- (Badischer Kunstverein, 2022)
Begun in 2007 by artists Daniel Gustav Cramer and Haris Epaminonda, The Infinite Library is composed of an archive of over 100 books made through the recombination of pages from one or more found publications. Each book is dismantled, modified, and reorganized. Pictures and pages—momentarily out of order—are brought together to shape yet another whole. The concept for each new volume develops gradually, starting from the content of the original book and the associations that unfold in the process of making. This publication fully catalogues the first 50 books in the series, and contains over 1600 photographic illustrations, 20 color inserted sheets, and a contextualizing essay by writer Brian Dillon presented in both English and German translations. Edited by Anja Casser and Jeff Khonsary. Co-published by Badischer Kunstverein
Produced in conjunction with the exhibition "The Infinite Library (Daniel Gustav Cramer and Haris Epaminonda)", Badischer Kunstverein, Karlsruhe, 6 July - 9 September 2012
Edition of/Auflage 1500
Keywords: Cramer, Daniel Gustav -- 1975-; Epaminonda, Haris -- 1980-; Buch -- Motiv; Ausstellungskatalog -- Badischer Kunstverein -- 06.07.2012-09.09.2012 -- Karlsruhe; Bildband